Analysis of Health Service Quality and Patient Satisfaction on Patient Loyalty in the Outpatient Installation of Aulia Blitar General Hospital - Muhamad Choirul Anam (Universitas STRADA Indonesia, 2023)
Quality of service is an important thing in services, especially health services in hospitals to provide satisfaction to patients and families. Satisfaction is the result of the good quality of the services provided so that there will be a feeling of comfort and safety for returning to the hospital or health service. The return of patients to the hospital for treatment is one proof of patient loyalty and patient loyalty to the hospital because they are satisfied with the quality of services provided. This study aims to determine the effect of quality of health services and patient satisfaction on patient loyalty in outpatient installations at Aulia Blitar General Hospital. This type of research uses observational analytic with cross sectional design.